“Nuakin Batu Kukuk” di Desa Tianyar, Karangasem - Hartawan, I Gusti Made Dharma; Wiradnya, I Kadek Restu (Bali Membangun Bali: Jurnal Bappeda Litbang, 2024)
Purpose: The purpose of this scientific work is to explain the rules for playing the cuckoo stone shrine in Tianyar Village, Karangasem Regency, Bali. Reseach methods: This research uses a qualitative approach. Data collection in this research used observation, interview and documentation techniques. The researchers used the technique of checking the validity of triangulation data with sources. Results and discussion: Tianyar Village is proven to have carried out ceremonies which are carried out before planting and when the harvest arrives. The aim is as a self-defense mechanism in order to maintain the existence of traditions and continuity of life as well as integration, namely the allocation of the value of natural resources as an expression of gratitude to foster a culture of mutual help, mutual assistance and mutual cooperation. Conservation and maintenance lead to production patterns between penyakap and land owners. Implication: The existence of cuckoo stone shrines is a rule of thumb in regulating and maintaining the continuity of life, such as carrying out ceremonies that are carried out before planting and when the harvest arrives.